2020
DOI: 10.14252/foodsafetyfscj.d-20-00017
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Estimation of Annual Committed Effective Dose of Radioactive Cesium by Market Basket Study in Japan from 2013 to 2019 after Fukushima Daiichi Nuclear Power Plant Accident

Abstract: Radionuclide contamination in foods has been a great concern after the Fukushima Daiichi Nuclear Power Plant (FDNPP) accident. To estimate time trends of daily intake and annual committed effective dose of radionuclides after the accident, radioactive cesium (r-Cs; 134 Cs and 137 Cs) and potassium-40 ( 40 K) in market basket (MB) samples prepared at 6-month intervals in periods from September 2013 to March 2019 in 15 regions of Japan were analyzed using γ-ray spectrometry. The annual committed effective dose o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In reality, only 2.5% of the food was contaminated with a dose that exceeded the provisional threshold by the time Ms. Komiyama, the Minister of Health, Labour and Welfare, advised that a new standard should be set to reduce the limit for the annual internal exposure dose from 5 mSv to 1 mSv. An assessment of internal exposure demonstrated an annual dose of 0.019 mSv 18) in Fukushima Prefecture, which is two orders of magnitude lower than the advised level of 1 mSv/y. This provisional standard was considered adequate.…”
Section: Radiation Exposure From Food Intake and Food Standardsmentioning
confidence: 81%
“…In reality, only 2.5% of the food was contaminated with a dose that exceeded the provisional threshold by the time Ms. Komiyama, the Minister of Health, Labour and Welfare, advised that a new standard should be set to reduce the limit for the annual internal exposure dose from 5 mSv to 1 mSv. An assessment of internal exposure demonstrated an annual dose of 0.019 mSv 18) in Fukushima Prefecture, which is two orders of magnitude lower than the advised level of 1 mSv/y. This provisional standard was considered adequate.…”
Section: Radiation Exposure From Food Intake and Food Standardsmentioning
confidence: 81%
“…There were no significant differences in overall consumption pattern between the eight regions through the two phases of our study. The 14 food groups for TDS samples were identical to those previously reported 21,22) : (I) rice and rice products, (II) cereals, seeds and potatoes, (III) sugars and confectioneries, (IV) fats and oils, (V) pulses, (VI) fruits, (VII) green vegetables, (VIII) other vegetables, mushrooms and seaweed, (IX) beverages, (X) fish and shellfish, (XI) meat and eggs, (XII) milk and dairy products, (XIII) other foods (e.g., seasonings), and (XIV) drinking water. In the actual preparation of the TDS samples, individual food items were arbitrarily selected from among various food items available in supermarkets in each region.…”
Section: Tds Samplesmentioning
confidence: 96%
“…Consequently, the monitoring of 134,137 Cs in organisms may need to continue until they decay naturally or dissipate in the environment to undetectable levels [4][5][6][7][8][9][10][11]. The processes of the resuspension of 134,137 Cs are not fully understood but many studies have concluded that the concentrations and exposure levels of radioactive Cs were well below regulatory levels, and that their contribution to the long-term exposure of the public from consuming foodstuffs has not been significant in recent years [12][13][14].…”
Section: Introductionmentioning
confidence: 99%